Managing Employee Participation based on OSHA’s Process Safety Management Requirements - Diana Abdul Majid, Noor; Zaini, Dzulkarnain; Mohd Shariff, Azmi (International Journal of Engineering and Technology, 2018)
A report published on 25 April 2016 stated that OSHA has issued 14 serious violations after an investigation conducted in a variety of industries including manufacturing, water treatment and oil and gas that violated OSHA's Process Safety Management (PSM) standard. One of the violations is related to the 29 CFR 1910.119(c)(2) which is employers did not consult with employees and their representatives on the conduct and development of the OSHAâ€™s PSM elements which are process safety information (PSI), process hazard analyses (PHA), training (TNG), mechanical integrity (MI), management of change (MOC), pre-start up safety review (PSSR), contractors (CON), incident investigations (II), emergency planning and response (EPR), compliance audit (CA) and trade secret (TS). 29 CFR1910.119(c)(2) is one of the requirements in the OSHAâ€™s PSM employee participation element. However, companies are still struggling to comply with this regulation due to unclear coverage and the implementation method for achieving compliance. Thus, this paper presents a framework and work-aid tool developed based on OSHAâ€™s PSM 29 CFR 1910.119(c) which are helpful to the industries as they provide structured technique to plan and implement an employee's participation management system to achieve compliance in implementing the OSHA PSM employee participation element.Â Â